Adenine alleviates iron overload by cAMP/PKA mediated hepatic hepcidin in mice. Issue 9 (30th March 2018) - Zhang, Yingqi; Wang, Xudong; Wu, Qian; Wang, Hao; Zhao, Lu; Wang, Xinhui; Mu, Mingdao; Xie, Enjun; He, Xuyan; Shao, Dandan; Shang, Yanna; Lai, Yongrong; et al.
Abstract : Hemochromatosis is prevalent and often associated with high rates of morbidity and mortality worldwide. The safe alternative iron‐reducing approaches are urgently needed in order to better control iron overload. Our unbiased vitamin screen for modulators of hepcidin, a master iron regulatory hormone, identifies adenine (vitamin B4) as a potent hepcidin agonist. Adenine significantly induced hepcidin mRNA level and promoter activity activation in human cell lines, possibly through BMP/SMAD pathway. Further studies in mice validated the effect of adenine on hepcidin upregulation. Consistently, adenine dietary supplement in mice led to an increase of hepatic hepcidin expression compared with normal diet–fed mice via BMP/SMAD pathway. Notably, adenine‐rich diet significantly ameliorated iron overload accompanied by the enhanced hepcidin expression in both high iron‐fed mice and in Hfe −/− mice, a murine model of hereditary hemochromatosis. To further validate this finding, we selected pharmacological inhibitors against BMP (LDN193189). We found LDN193189 strongly blocked the hepcidin induction by adenine. Moreover, we uncovered an essential role of cAMP/PKA‐dependent axis in triggering adenine‐induced hepcidin expression in primary hepatocytes by using 8 br cAMP, a cAMP analog, and H89, a potent inhibitor for PKA signaling. These findings suggest a potential therapeutic role of adenine for hereditary hemochromatosis. Abstract : Unbiased vitamin screen for hepcidin modulators identifies adenine (vitamin B4) as a potent hepcidin agonist. Adenine‐induced hepcidin in mice significantly reduced iron overload through cAMP/PKA‐dependent BMP/SMAD1/5/8 pathways. Iron overload is prevalent and has been associated with many related pathological conditions. Adenine (vitamin B4) was identified as a potent hepcidin agonist through a functional screen of vitamin library for modulating expression of hepcidin, a master regulator of iron homeostasis. Notably, dietary adenine supplementation significantly attenuated iron overload in both high‐iron diet fed wildtype mice and in Hfe knockout mice through cAMP/PKA‐modulated downstream BMP/SMAD signaling pathways. The findings open a new avenue for treating iron overload and its related disorders. Further studies are warranted for the potential clinical implications.